Navigating the Cairene Table: Food and Family between What Is Ideal and What Is Real - Afify, Iman (AUC Knowledge Fountain, 2022)
Our daily encounters with food, especially during our childhood, play a crucial role in shaping and informing our identity and our habitus. In this research, by using multimodal and auto ethnography, I argue that due to the guiding path that our senses carve for us, we make sense and contextualise our surroundings through our senses, and not only the five senses of vision, smell, taste, hearing, and touch, but also through our inner senses of time and temporality, and how time and memory play an important role in the registration of our surroundings through our bodies and senses. I am dealing with the senses as a guide for us, starting from childhood and planting the seeds of sensorial ideologies and contextualisation through our exposure to different sensorial elements via food. The first time of smelling a breakfast item that later on became a favourite; tasting tea for the first time in a family gathering and having the memory stamped in mind by the strong earthy flavour of the beverage; the sound of food sizzling in a pan, signalling the preparation of a feast; the first touch of a bread loaf brushing against one’s palm, tethering its warmth and its texture into one’s hands, are all examples of first encounters of a life-long sensuous and ideological affair with food. How do the passing interactions with food during our childhood shape our future understandings of our surrounding world(s)? The senses not only played an important role in understanding the self as part of my autoethnography, but the senses also helped in understanding the other aspects of this research being gender, kinship, social representation, and class dynamics. When discussing food and family, discussing gender and kinship is inevitable. How does food and family intertwine under the guises of gender and kinship? And why can food and family never be confined within the limitations offered by binaries? Although the Egyptian society is considered by Egyptians and non-Egyptians alike as patriarchal, I describe that this is not the case when it comes to what is being seen on the façade of a household vis-à-vis what actually takes place within the confinements of the domestic sphere. The ideal image of a family might be known as a patriarch/breadwinner being the man of the house, but from fieldwork, I argue that this is not always the case, but far from it. The factuality of the matter is far more complex and multi-layered than to be deemed either purely patriarchal or radically matriarchal. There are aspects and details that go into each and every household that give it its own context and constitute how the household is run and maintained. Overlooking the influence of capitalism and how it goes hand in hand with patriarchy will also misbalance the scales of my argument; thus, rendering it essential to be pointed out. Finally, how can the supermarket be looked at as a social simulacrum of class and class identity? What are the sensorial differences between the confined supermarket and the open souq? I showcase that the places that sell food (i.e., supermarkets and souqs) not only sell the product, but also sell a class identity informed by the brand bought by the consumer. The supermarket is not only a place of shopping, but it is also a systematic place of identity distribution. I argue that, unlike the haphazardness of the souq, the supermarket is hyper-organised to the point of sensorial sterility and is deprived of the social dramatisation of daily interactions.